The situation of people suffering from diabetes in Poland. Needs of changes in the health care system. - Grudziąż-Sękowska, Justyna; Pruszyński, Jacek; Goryński, Paweł; Jasik, Agnieszka; Gumowski, Piotr; Religioni, Urszula; Ostrowski, Janusz; Kobuszewski, Bartosz (Wiedza Medyczna, 2022)
Diabetes mellitus affects about 3 million Poles, which is almost 8% of the population. It belongs to the national health priorities defined in the regulation of the Minister of Health. If poorly controlled, it leads to the development of many serious complications, both acute and chronic. It excludes people who are often of productive age from an effective, satisfactory life, and therefore causes an increase in public costs due to health and social insurance, and a decrease in state budget revenues from production and consumption. Measures taken in the areas of: population prevention addressed to the entire population, with particular emphasis on vulnerable groups, early diagnosis of diabetes and its effective treatment, and support for patients preventing disability and exclusion, should help reduce these costs.<span class="EOP SCXW244632308 BCX0" data-ccp-props=""201341983":0,"335551550":6,"335551620":6,"335559739":160,"335559740":360,"469777462":[916,1832,2748,3664,4580,5496,6412,7328,8244,9160,10076,10992,11908,12824,13740,14656],"469777927":[0,0,0,0,0,0,0,0,0,0,0,0,0,0,0,0],"469777928":[1,1,1,1,1,1,1,1,1,1,1,1,1,1,1,1]">